2009
DOI: 10.1539/joh.k8004
|View full text |Cite
|
Sign up to set email alerts
|

Do We Recover from Vacation? Meta‐analysis of Vacation Effects on Health and Well‐being

Abstract: The aim of this metaanalysis is to investigate to what extent vacation has positive effects on health and well-being, how long such effects endure after work resumption, and how specific vacation activities and experiences affect these relationships. Methods: Based on a systematic l i t e r a t u r e s e a r c h ( P s y c I n f o , M e d l i n e ) a n d methodological exclusion criteria, in a stepwise approach, 7 studies were selected and reviewed. Effect sizes (Cohen's d) were calculated i) for every outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
198
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(240 citation statements)
references
References 25 publications
(183 reference statements)
15
198
3
4
Order By: Relevance
“…Additionally, the findings shed light on the insufficient length of vacation between the end of a competitive season and a new pre-season-some coaches hardly take a break (McChesney & Peterson, 2005). However, authors of a meta-analysis (de Bloom, Kompier, Geurts, de Weerth, Taris, & Sonnentag, 2009) argued that the beneficial effects of recovery after vacation on health and well-being fade out shortly after work resumption. Consequently, prevention of higher levels of exhaustion is most likely to be efficient when making changes in the work environment, rather than relying on long term effect from recovery between seasons.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the findings shed light on the insufficient length of vacation between the end of a competitive season and a new pre-season-some coaches hardly take a break (McChesney & Peterson, 2005). However, authors of a meta-analysis (de Bloom, Kompier, Geurts, de Weerth, Taris, & Sonnentag, 2009) argued that the beneficial effects of recovery after vacation on health and well-being fade out shortly after work resumption. Consequently, prevention of higher levels of exhaustion is most likely to be efficient when making changes in the work environment, rather than relying on long term effect from recovery between seasons.…”
Section: Discussionmentioning
confidence: 96%
“…The positive effects which vacationing has on happiness are mostly limited to the duration of the holiday trip itself (De Bloom et al 2010;Nawijn 2010) and a brief phase of anticipation ) and afterglow (De Bloom et al 2009;. It seems fair to say that holiday trips offer mostly an uplift in mood and the kind of satisfaction which Veenhoven (2010) would regard as a pleasure, a passing kind of satisfaction related to a part of life.…”
Section: Discussionmentioning
confidence: 99%
“…A number of pre-test/post-test design studies have found higher levels of happiness (Gilbert and Abdullah 2004;) and other positive effects, such as decreased levels of stress and generally better health, after a holiday trip (Strauss-Blasche et al 2000;Westman and Eden 1997;Westman and Etzion 2001), although these effects fade out rather quickly (De Bloom et al 2009). …”
Section: Earlier Research On Tourism and Happinessmentioning
confidence: 99%
“…These prolonged physiological stress responses can be amplified by ruminating thoughts about past and potential future stressors (Geurts & Sonnentag, 2006) and may disturb the person's homeostatic balance (''allostasis,'' McEwen, 1998), that is, Although vacation is probably the most powerful prototypical respite occasion for working individuals, as yet surprisingly few researchers have addressed its impact on recovery from work. A recent meta-analysis of vacation research (De Bloom et al, 2009) identified only seven studies that met a set of minimum methodological requirements for studying the effects of vacation on health and well-being. The results of these studies suggest that vacation has positive, although weak effects on health and well-being, and that these effects fade out quickly after returning home.…”
Section: Introductionmentioning
confidence: 99%